2015
DOI: 10.1111/codi.12886
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high‐risk Dukes B colorectal cancer by microRNA expression profiling: a preliminary study

Abstract: The study suggests that the development of metastasis in Dukes B tumours may be predictable based on the miRNA expression of miR-15b and miR-135b. This requires further study on a much larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
1
1
1
Order By: Relevance
“…However, the exact roles of miR-15b in CRC remain elusive. Our results are compatible with the report by Aslam et al (2015), which stated that expression of miR-15b was significantly downregulated in “high-risk B” tumors compared with Dukes A, “low-risk B” or C without metastasis in CRC. However, different groups reported that miR-15b could promote epithelial-mesenchymal transition (EMT) and tumor metastasis in pancreatic cancer, as well as inhibit apoptosis and correlate with poor prognosis in malignant melanoma (Satzger et al., 2010, Zhang et al., 2015), reflecting the complexity of regulation and functions of miRs in the context of different tumors.…”
Section: Discussionsupporting
confidence: 93%
“…However, the exact roles of miR-15b in CRC remain elusive. Our results are compatible with the report by Aslam et al (2015), which stated that expression of miR-15b was significantly downregulated in “high-risk B” tumors compared with Dukes A, “low-risk B” or C without metastasis in CRC. However, different groups reported that miR-15b could promote epithelial-mesenchymal transition (EMT) and tumor metastasis in pancreatic cancer, as well as inhibit apoptosis and correlate with poor prognosis in malignant melanoma (Satzger et al., 2010, Zhang et al., 2015), reflecting the complexity of regulation and functions of miRs in the context of different tumors.…”
Section: Discussionsupporting
confidence: 93%
“…7,8 New research showed that mi RNA is closely related to the development of tumors and plays an important role in the malignant characteristics of tumors. 9,10 At present, various miRNAs such as miR-25, miR-98, miR-34a, miR-194, mi R-495 and miR-365 have been confirmed to be involved in proliferation, differentiation, apoptosis and drug resistance of breast cancer cells. [11][12][13] Therefore, based on the regulation of miRNAs, further research on breast cancer-related miRNA and its mechanism of action can provide new ideas and directions for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies have also found an association between higher expression levels of FER1L4 and tumor suppressor functions [ 57 ], and between up-regulation of the miR-135b and BST2 genes and both metastatic [ 58 ] and poor prognosis colorectal tumors [ 59 ]. In this regard, Gaedcke et al [ 60 ] and Aslam et al [ 61 ] have previously reported an association between down-regulation of miR-135b in Dukes’ stage B sCRC patients who developed metastatic disease and a shorter disease-free survival; although these results are fully in line with our observations, they could not be systematically confirmed by others [ 58 , 59 ]. In turn, the greater BST2 gene expression levels found here among non-MTX tumors, could potentially be more related to the immunomodulatory role of stromal cells expressing BST2 in non-MTX sCRC, rather than the tumor cell-specific expression levels per se ; this would contribute to explain, at least in part, the apparent discrepant findings in the literature [ 62 ].…”
Section: Discussioncontrasting
confidence: 70%